A Microscopic Prediction Model for Traffic Noise in Adjacent Regions to Arterial Roads - LI, Ming; LIU, Jizhou (Archives of Acoustics, 2023)
Traffic noise in big cities impacts the people who live and work in high-rise buildings alongside arterial roads. To determine this impact magnitude, this paper proposes and validates a microscopic level method that locally predicts the total noise level and the spectral characteristics of traffic flow in the near-road region. In the proposed method, the vehicles on the road are considered as multiple queues of moving point sound sources with ground reflection considered. To account for the flow of vehicles on the road, traffic field data, and individual vehicle noise source models are also employed. A field measurement is conducted to validate the proposed method. Results comparison shows that the predicted and the measured overall A-weighted sound pressure level and A-weighted noise spectra are within 3 dBA and 5 dBA, respectively. Based on the validated method, the spatial distribution of traffic noise near the arterial road is investigated for different traffic scenarios.